BATIK WASTEWATER MANAGEMENT ANALYSIS BY INTEGRATED COMUNAL, CASE STUDY OF KAMPOENG BATIK LAWEYAN - Ravita Sari; Tri Edhi Budhi Soesilo; Herdis Herdiansyah (AGRIBUSINESS JOURNAL, 2019)
Batik industry is one of the industries that produces wastewater which contains harmful chemicals. In order to maintain the quality of the environment, it is necessary to have a wastewater management system. The region which has conducted the comunal waste management system is Kampoeng Batik Laweyan. However, this effort of waste management system has not optimal yet. The purpose of this paper is to analyze wastewater management system in Kampoeng Batik Laweyan. The approach of this paper is a quantitative approach, using mix-metode. The analysis of the wastewater management system has been done by assesing 4 aspects such as technical aspect, managerial aspect, economic aspect, and environmental aspect. The wastewater management system has provided good results in technical dan managerial aspects only. For the economic and the environment aspects need to be upgraded since they have not shown any important improvements. Through this paper it is expected to create a substantial improvement in economic and environmental aspects.Keyword: Batik waste, Laweyan, management, wastewater, WWTP.